Factors associated with performance decrements in elite athletes during exercise under hot and humid ambient conditions - Peggen, M. A. G.; Bongers, C. C. W. G.; de Korte, J. Q.; Alkemade, P.; Daanen, H. A. M.; Hopman, M. T. E.; Eijsvogels, T. M. H. (International Journal of Sports Physiology and Performance, 2026)
Purpose: Exercise performance is compromised in hot and humid conditions compared to temperate circumstances. However, it remains unclear which factors predispose individuals to either small or large performance decrements. This study aimed to identify factors associated with performance decrements in elite athletes during exercise under hot and humid ambient conditions.